Robotic-assisted versus laparoscopic bowel anastomoses: randomized crossover in vivo experimental study - Haney, Caelán Max; Kowalewski, Karl-Friedrich; Schmidt, Mona Wanda; Lang, Franziska; Bintintan, Vasile; Fan, Carolyn; Wehrtmann, Fabian; Studier-Fischer, Alexander; Felińska, Eleni Amelia; Müller, Beat P.; Nickel, Felix (Surgical endoscopy and other interventional techniques, 2023)
Initial learning curves are potentially shorter in robotic-assisted surgery (RAS) than in conventional laparoscopic surgery (LS). There is little evidence to support this claim. Furthermore, there is limited evidence how skills from LS transfer to RAS.
Online veröffentlicht: 18. April 2023
Gesehen am 02.04.2024